2020
DOI: 10.1080/10503307.2020.1804084
|View full text |Cite
|
Sign up to set email alerts
|

Sudden gains and large intersession improvements in internet-based psychodynamic treatment (IPDT) for depressed adolescents

Abstract: Objective: Sudden gains (SGs) have often been found associated with better treatment outcome across different psychiatric disorders. However, no studies have evaluated SGs in internet-based treatment targeting adolescent depression. Method: The sample consisted of 66 adolescents diagnosed with major depressive disorder, attending psychodynamic internetbased treatment. Effects of SGs were evaluated at posttreatment and 6-month follow-up. We also evaluated effects of large intersession improvements (LIIs; sudden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Following this study, Mechler et al (2020) Shalom and Aderka (2020) in their meta-analysis reported the average reversal rate to be 31.5%…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Following this study, Mechler et al (2020) Shalom and Aderka (2020) in their meta-analysis reported the average reversal rate to be 31.5%…”
Section: Discussionmentioning
confidence: 75%
“…This study also used more sophisticated analyses to examine symptom and functioning changes over time because MLM was used. MLM has only recently begun to be used in the SGs literature (e.g., Mechler et al, 2020;Wiedemann et al, 2020) and is a favourable statistical approach because it accounts for clustering effects as well as repeated measures over time.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations